In-Silico Design of a PIN1/ABCC5-Targeted Multi-Epitope Vaccine for Nasopharyngeal Cancer - Ashiila, Putri; Gustiananda, Marsia (Universitas Bio Scientia Internasional Indonesia, 2026)
Nasopharyngeal Carcinoma (NPC) is a rare malignancy. However, it is the fourth most common cancer affecting both sexes in Indonesia, and research on NPC remains limited. NPC is related to Epstein-Barr Virus (EBV) infection, making it a potential target for immunotherapy strategies. Developing a multi-epitope-based NPC vaccine targeting tumor-overexpressed antigens may evoke an immune response against cancer cells and benefit patients with advanced cancer stages or those resistant to treatment. Four cytotoxic (CTL) and one helper T-cell (HTL) epitopes from PIN1 were identified using NetMHCpan and NetMHCIIpan algorithms, respectively. Whereas from ABCC5, five CTL and four HTL epitopes were identified using the same algorithms. These epitopes were found to have good coverage across the Indonesian population, with population coverage analysis showing 99% coverage for human leukocyte antigen (HLA) Class I and 95% for HLA Class II. Having fulfilled other criteria such as immunogenicity, IFN-γ-inducing ability, and non-homology to human peptides, the epitopes were assembled into a vaccine construct together with E. coli and Bacillus as adjuvants and appropriate linkers. The construct was shown to have good physicochemical characteristics and the ability to induce CTL and HTL responses, which stem from the engagement of the vaccine with toll-like receptor 4 (TLR4) as revealed by docking simulations.